THE EFFECTIVENESS OF ATHLETE DEVELOPMENT AT THE DEPARTMENT OF YOUTH, SPORTS, AND TOURISM (DISPORAPAR) OF BALANGAN REGENCY - Muhammad Abdillah Nazmi Ramadhan; Arpandi Arpandi; Moh. Fajar Noorrahman (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
This study was driven by the gap between the strategic role of the Balangan Regency Sports and Tourism Office (Disporapar) as an incubator for high-achieving athletes and the reality on the ground, which remains trapped by seasonal development patterns and limited infrastructure. With the aim of deeply analyzing development effectiveness, this study adopted Duncan's theoretical framework (as cited in Mokoginta et al., 2021), which highlights vital dimensions such as goal achievement, integration, and adaptation. Using a descriptive qualitative approach that processed data from interviews, observations, and documentation, the analysis confirmed that the current performance of athlete development is ineffective. This failure is clearly identified in the goal achievement dimension, which lacks transparent medal target parameters, and in the integration dimension, which is hampered by convoluted bureaucratic procedures and a merely ceremonial socialization pattern. Furthermore, fundamental weaknesses were found in the adaptation aspect, where training continuity is often interrupted outside the competition season and the minimal adoption of sports science technology in training facilities. In conclusion, the organization's inability to orchestrate resources in an integrated manner is a major obstacle to long-term achievement. Therefore, a radical transformation in facility management and consistent standardization of training programs are absolute solutions that must be implemented immediately to improve the competence and competitiveness of regional athletes.